Program Kemitraan Masyarakat (PKM) Taman Kanak-Kanak Kota Pontianak Kalimantan Barat - Ferry Hadary (Universitas Muhammadiyah Pontianak, 2018)
ABSTRACT Partner-1 of this Community Partnership Program (Program Kemitraan Masyarakat/PKM) is Primanda UNTAN Kindergaten, and Partner-2 Bina Insan Kindergaten. Both partners have problems about learning facilities Educational Game Tools (Alat Permainan Edukatif/APE) which is very minimal both indoor and outdoor. When teaching is still limited to factory made APE, while there are still many local natural resource potentials in West Kalimantan that can be used to create. Teachers are still lacking in socialization/training about the use of local natural resources. Special problems that found in partner-2 are learning methods still focused on reading, writing, and calculating (calistung). Parents in partner-2 want learning in kindergaten to focus on calistung learning. The purpose of this PKM, are: (1) knowledge sharing and appropriate technology through interactive multimedia approaches based on local natural resources in the shaped animation; (2) hold socialization/training to teachers and parents about the child's learning system according to their age; (3) interactive multimedia application demonstration in class. The enthusiastic of both partner's shows that this activity is needed by them to help them fix the problems that exist in each kindergaten. The socialization activity ended with a discussion in the form of questions and answers from participants related to the way of learning for kindergaten children using APE and interactive multimedia. The expectation of this activity is the knowledge sharing and technology to the teachers, so that the teaching and learning process becomes more enjoyable and understandable by kindergaten children using APE and interactive multimedia. Keywords: APE, Bina Insan Kindergaten, Multimedia, Primanda Kindergaten,